Update on: Shigella new serogroups/serotypes and their antimicrobial resistance. (28th November 2016) - Muthuirulandi Sethuvel, D.P.; Devanga Ragupathi, N.K.; Anandan, S.; Veeraraghavan, B.
Abstract: Shigellosis represents a major burden of disease in developing countries. A low infectious dose allows the disease to be spread effectively. Although shigellosis is mostly a self‐limiting disease, antibiotics are recommended to reduce deaths, disease symptoms and organism‐shedding time. However, in India, antimicrobial resistance among the genus Shigella is more common than among any other enteric bacteria. Notably, new serotypes or subserotypes in Shigella are reported from various parts of the world. Identification of new subserotypes of Shigella spp. is becoming a major issue as these strains are nontypeable by conventional serotyping. The commercially available antisera may not cover all possible epitopes of the O lipopolysaccharide antigen of Shigella serotypes. Therefore, molecular methods which most closely approach the resolution of full serotyping are necessary to identify such strains. In addition, the knowledge of a prevalent serotype in various geographic regions may assist in formulating strategies such as the development of a vaccine to prevent infection especially when the immunity to disease is serotype specific, and to understand the disease burden caused by new Shigella serotypes.